Operationalising basic needs: A few fundamental reflections - Wilfried Lütkenhorst (Intereconomics, 1982)
Development research (not so much practical development policy-making) has been recently marked by an increased orientation towards the satisfaction of basic needs. This raises the question as to whether indicators exist which could adequately provide for a sufficiently exact operationalisation of at least the basic physical human needs (nutrition, health, shelter, clothing and education). This would enable improved measurement of the degree to which target levels have in fact been reached and an evaluation of alternative economic strategies. The following article sets out to examine possible ways of operationalising basic needs.
Keywords: 330; Development Strategy